Ancient Damascus: A Historical Study of the Syrian City-State from Earliest Times until its Fall to the Assyrians in 732 B.C.B. - Pitard, Wayne Thomas
Diss.; Order No. DA8222690. Cf. DissAbstr 43 (1983) 2416-A.